Ḵẖut̤ūt̤-i Shiblī banām muḥtarmā Zuhrā Begam ṣāḥibah Faiz̤ī va ʻAt̤iyah Begam ṣāḥibah Faiz̤ī - Shibli Numani, Muhammad, 1857-1914 (SAMP early 20th-century Indian books project ;, 1930)
Collection of letters.